2006
DOI: 10.1242/jcs.02970
|View full text |Cite
|
Sign up to set email alerts
|

Syndecan-1 regulates αvβ5 integrin activity in B82L fibroblasts

Abstract: B82L mouse fibroblasts respond to fibronectin or vitronectin via a syndecan-1-mediated activation of the αvβ5 integrin. Cells attached to syndecan-1-specific antibody display only filopodial extension. However, the syndecan-anchored cells extend lamellipodia when the antibody-substratum is supplemented with serum, or low concentrations of adsorbed vitronectin or fibronectin, that are not sufficient to activate the integrin when plated alone. Integrin activation is blocked by treatment with (Arg-Gly-Asp)-contai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
85
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 102 publications
(88 citation statements)
references
References 74 publications
3
85
0
Order By: Relevance
“…The Sdc1 regulates the activities of several integrins, including ␣v␤3, ␣v␤5, and ␤4 integrins. [43][44][45][46] Although the FN matrix assembly appears to be initiated mainly by Arg-Gly-Asp-binding integrin ␣5␤1, 47,48 alternative FN-binding integrin receptors (eg, ␣v␤3, ␣4␤1, and ␣v␤1) can also support this process once properly activated. 33,49 -52 It is possible that Sdc1 induction activates integrins other than ␣5␤1 and initiates an alternative assembly pathway, thus resulting in an ECM that is structurally/compositionally different from that assembled under the control of ␣5␤1.…”
Section: Discussionmentioning
confidence: 99%
“…The Sdc1 regulates the activities of several integrins, including ␣v␤3, ␣v␤5, and ␤4 integrins. [43][44][45][46] Although the FN matrix assembly appears to be initiated mainly by Arg-Gly-Asp-binding integrin ␣5␤1, 47,48 alternative FN-binding integrin receptors (eg, ␣v␤3, ␣4␤1, and ␣v␤1) can also support this process once properly activated. 33,49 -52 It is possible that Sdc1 induction activates integrins other than ␣5␤1 and initiates an alternative assembly pathway, thus resulting in an ECM that is structurally/compositionally different from that assembled under the control of ␣5␤1.…”
Section: Discussionmentioning
confidence: 99%
“…Sdc1 regulates the activation of avb3 and avb5 integrins on mammary carcinoma cells, fibroblasts and endothelial cells Beauvais et al, 2009;Beauvais and Rapraeger, 2003;McQuade et al, 2006). Activation of avb3 and/or avb5 integrin stimulates adhesion, spreading and migration of tumor and endothelial cells, with clear consequences on tumor progression.…”
Section: Introductionmentioning
confidence: 99%
“…Ligation and clustering of Sdc1, either on cells in suspension or bound to an immobilized ligand (Sdc1 antibody or VN), activates the avb3 and/or avb5 integrin, thus stimulating cell spreading and migration Beauvais et al, 2009;Beauvais and Rapraeger, 2003;McQuade et al, 2006). Silencing of human Sdc1 expression by species-specific siRNAs blocks integrin activation, which can be rescued by ectopic expression of either full-length mouse Sdc1 or the glycosylphosphatidylinositolanchored mouse Sdc1 ectodomain alone (GPI-S1ED) McQuade et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Syndecan-1 is a heparan sulfate proteoglycan acting as a transmembrane receptor. Its coupling with other receptors such as integrins might induce cell adhesion and angiogenesis [12]. It was suggested that YKL-40 could activate key signaling cascades-PI3K/AKT and MAPK/ERK resulting in high rate of cell proliferation and tumor cell survival [13,14].…”
Section: Ykl-40 Ligandsmentioning
confidence: 99%